Re(I) sensitised near-infrared lanthanide luminescence from a hetero-trinuclear Re2Ln array. - Pope, S; Coe, B; Faulkner, S (2004)
The trinuclear complexes Re2Ln (Ln = Nd, Yb or Er) contain two Re(I) tricarbonyl units linked to a DTPA binding site via 2,2'-bipyridyl ligands; Ln(III)-centred emission is sensitised by the Re(I) MLCT excited states.